The Impact of Service Quality on Students' Satisfaction and the Word-of-Mouth: The Case of the University of Rijeka Departments (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The purpose of this paper is to determine the impact of service quality perceived by science, technology, engineering and mathematics (STEM) and information-communication (IC) students of the University ofRijeka Departments on students' satisfaction and positive word-of-mouth. Based on the extensive literature review, the survey method was used to explore the relationships between the following variables: service quality, students' satisfaction, and word-of-mouth. The data were collected through an online self-administrated structured questionnaire administered to undergraduate and graduate STEM and IC students of the University of Rijeka Departments using Google Docs Forms. The findings provide some important insights into how the service quality impacts the students' satisfaction and word-of-mouth, in a Croatian higher education context. A high positive significant impact of service quality on students' satisfaction and word-of-mouth clearly indicates that it is an imperative for higher education sector. Based on the results and remarks of this study improvements can be planned and concluded across all dimensions. Policy makers in the industry in general and in the higher education sector, in particular, may benefit from the findings of this study.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.